Magnetoencephalography (MEG): Past, current and future perspectives for improved differentiation and treatment of epilepsies - Stefan, Hermann; Trinka, Eugen (Seizure-European Journal of Epilepsy, 2017)
In addition to visual analysis digital computerized recording of electrical and magnetic fields by using EEG and MEG opened a new window for research concerning improved understanding of pathophysiology, diagnosis and treatment of epilepsies. In the last 25 years MEG was used more and more in clinical studies concerning localization of focal epileptic activity, functional cortex and network analysis. Simultaneous MEG/EEG recording and analysis offer the use of complimentary information increasing the sensitivity for tracing primary epileptic activity. Combined MEG/Stereo-EEG recordings showed that MEG noninvasively identified regional interictal networks. The current role of MEG for presurgical evaluation with regard to noninvasive localization in MRI normal patients, guiding of invasive electrode implantation and correlation to postoperative outcome after epilepsy surgery is stressed. Challenges and future opportunities for MEG in clinical epileptology are discussed.
EVALuna2:36360